Identification of Microplastics in the Upper Cimanuk Watershed and Waste Management Analysis in Garut Regency, Indonesia - Afiefah Salsabila; Sunardi; Titin Herawati (Industrial and Domestic Waste Management, 2026)
The Cimanuk River was a vital component supporting water resources in West Java. However, further downstream, the water quality decreased due to industrial and household waste disposal. Plastic pollution was a serious issue because plastics in water degraded into microplastics, which were harmful to both ecosystems and human health. This study aimed to assess the abundance and characteristics of microplastics in the Upper Cimanuk Watershed and to explore how waste management was implemented in Garut Regency. The water sampling method for microplastic analysis used non-probability sampling with a purposive sampling technique. The waste management analysis was a descriptive study using a qualitative approach. Microplastics were found in the waters of the Upper Cimanuk Watershed, with the highest abundance recorded at Station 8 (2.14 particles/liter) and the lowest at Station 1 (0.62 particles/liter). The microplastics identified were dominated by fragments (52%), black-colored particles (47%), and sizes smaller than 1 mm or small microplastics (97%). These findings reflected a high level of microplastic pollution related to human activities around the river. Waste management in Garut Regency had not met its targets, leading to plastic accumulation that could form microplastics. Improvements in facilities, community participation, and policies were needed to control pollution and protect the environment. The results of this study provided baseline data that could inform stakeholders in the Upper Cimanuk Watershed for effective watershed management planning.